Employee-Related Factors Influencing Health and Safety in The Ghanaian Construction Industry: A Confirmatory Factor Analysis of Professionals’ Perspectives - Akomah, Benjamin Boahene; Ramani, Prasanna Venkatesan (International Journal of Occupational Safety and Health, 2024)
Introduction: Employees’ gross disregard for health and safety issues in the construction industry is worrying. The paper aimed to ascertain the potential contributions of employees in restoring trust in health and safety within the sector. Methods: This study utilised a strictly quantitative research methodology. The study started with a comprehensive literature analysis to ascertain the employee-related variables that may impact health and safety outcomes within the construction sector of Ghana. During the process of searching, eleven important factors were identified, modified, and designed into a questionnaire for data gathering. In order to fulfil the objectives of the study, a total of 635 participants, consisting of experts from diverse backgrounds within the sector, were chosen using a simple random selection method. The participants were then given questionnaires in both hardcopy form and Google Forms. Results: The study had a response rate of 71.5%, indicating a substantial level of participation from the experts involved. Additionally, the data analysis demonstrated that the experts have significant expertise in the field under investigation. It was discovered that employee safety responsibilities and compliance behaviours are crucial roles that can contribute to the improvement of health and safety in the sector. The most significant variable that could enhance health and safety in the industry was the reporting of employees’ complaints regarding health and safety to supervisors - ESR2. The component accounted for 0.775, or 77.5%, of the variability in the latent construct of ESR. Conclusion: The active participation of employees in fulfilling their occupational health and safety (OHS) legal obligations is vital. This can be achieved by diligently utilising personal protective equipment (PPE), fostering a sense of organisational safety citizenship behaviour and ownership, and demonstrating the willingness to report any health and safety concerns to supervisors. These factors collectively constitute the fundamental elements of employees’ contribution to health and safety.